2006
DOI: 10.1021/jp061053r
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of the Properties of N−H···N, Noncooperativities, and Intermolecular Interactions in Linear trans-Diazene Clusters up to Ten Molecules

Abstract: We investigate aspects of N-H...N hydrogen bonding in the linear trans-diazene clusters (n=2-10) such as the N...H and N-H lengths, n(N) --> sigma(N-H) interactions, N...H strengths, and frequencies of the N-H stretching vibrations utilizing the DFT/B3LYP theory, the natural bond orbital (NBO) method, and the theory of atoms in molecules (AIM). Our calculations indicate that the structure and energetics are qualitatively different from the conventional H-bonded systems, which usually exhibit distinct cooperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…However, the spectra band of PEI modified TiO 2 exhibited a blue shift with larger E g of 2.67 eV. This blue shift is possibly due to n-σ* transition of imine (-NH) in PEI macromolecules [49] . Consequently, the narrow band gap of PSS-TiO 2 in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…However, the spectra band of PEI modified TiO 2 exhibited a blue shift with larger E g of 2.67 eV. This blue shift is possibly due to n-σ* transition of imine (-NH) in PEI macromolecules [49] . Consequently, the narrow band gap of PSS-TiO 2 in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The cooperativity of hydrogen bonds has received intensive theoretical25–37 and experimental research 38–40. Wu have suggested cooperativity in both α‐ and 3 10 ‐helices and in sheets of unnatural β‐polyglycines but little or none in β‐sheets of the natural α‐polyglycines 10–12.…”
Section: Introductionmentioning
confidence: 99%
“…Dannenberg and coworkers reported extensive Hartree–Fock, density functional theory (DFT), and second‐order Møller–Plesset perturbation theory (MP2) calculations on linear hydrogen‐bonded systems consisting of linear chains of urea14, 15 and formamide molecules 16–18. They suggested the unusually large cooperative hydrogen bonding in formamide chains to the following electronic effects: (1) pairwise electrostatic interactions (mainly long‐range dipole–dipole interactions), (2) nonpairwise short‐range (mutual) polarization, and (3) resonance‐assisted hydrogen bonding 32, 33. Baker and coworkers have studied the cooperativity of hydrogen‐bonded interactions in a model system for α‐helix formation and suggested that nonpairwise electronic effects account for half of the total cooperativity that is observed in this system 41.…”
Section: Introductionmentioning
confidence: 99%
“…When a small quantity of charge is transferred between the two urea molecules, The charge transfer (q HB ) of urea monomers as a consequence of the n O !r* NAH interaction between n O to NAH antibonding, r* NAH , can be used to characterize the amount of cooperative effects in the urea clusters. Recently, it has been widely shown that for H-bonded clusters, the calculated q HB values reasonably correlate with the number of monomer in the cluster [52,53]. However, the results collected in Table IV show that the calculated q HB value for central units of decamer cluster (4.14 Â 10 À3 au) is more than 200% of the dimer (1.92 Â 10 À3 au), reflecting the strong cooperative effects in the linear urea clusters.…”
Section: Charge Transfermentioning
confidence: 99%